Radioprotection of deinococcal exopolysaccharide BRD125 by regenerating hematopoietic stem cells - Park, Hae Ran; Lee, Ji Hee; Ji, Hyun Jung; Lim, Sangyong; Ahn, Ki Bum; Seo, Ho Seong (Frontiers in Oncology, 2022)
There is a substantial need for the development of biomaterials for protecting hematopoietic stem cells and enhancing hematopoiesis after radiation damage. Bacterial exopolysaccharide (EPS) has been shown to be very attractive to researchers as a radioprotectant due to its high antioxidant, anti-cancer, and low adverse effects. In the present study, we isolated EPS from a novel strain, Deinococcus radiodurans BRD125 that produces high EPS and investigated its application as a radioprotective biomaterial. It was confirmed that EPS isolated from EPS-rich D. radiodurans BRD125 (DeinoPol-BRD125) was found to have a higher level of free radical scavenging effect and reduced irradiated-induced apoptosis. In addition, bone-marrow and spleen cell apoptosis in irradiated mice was significantly reduced with DeinoPol-BRD125 administration. DeinoPol-BRD125 enhanced the expression of hematopoiesis-related cytokines such as GM-CSF, G-GSF, M-CSF, and SCF and thereby enhancing hematopoietic stem cells protection and regeneration. Taken together, our findings are the first reports to discovery the immunological mechanism of a novel radioprotectant, DeinoPol-BRD125 which might be proposed as an ideal radioprotective and radiation mitigating agent as a supplement drug during radiotherapy.